Post Kidney Transplant Early Recurrence of Membranous Nephropathy with Significant Proteinuria A Case Report (Pakistan Journal of Kidney Diseases, 2022)
Following renal transplantation, membranous nephropathy recurs in a significant number of patients. It can recur either early or late post kidney transplantation. Early recurrence is less commonly reported as patients remain clinically asymptomatic and it is diagnosed only on protocol biopsies. Majority of post-transplant recurrence occurs late, when patients develop clinical features. In the current report, we describe a patient who developed recurrent membranous nephropathy within 3 months of transplantation with full-blown clinical picture, which is uncommon.
Keywords: Kidney transplant; membranous nephropathy; recurrence; AntiPLA2r antibody; primary glomerulonephritis